Predicting neck abscess with contrast-enhanced computed tomography - Lim, Melisa Seer Yee; Abdul Rahim, Noraini; Ngah, Ning Ajleaa; Abdul Aziz, Yang Faridah; Subha, Sethu Thakachy (Hindawi Publishing Corporation, 2014)
Neck abscesses are difficult to diagnose and treat. Currently, contrast-enhanced computed tomography (CECT) is the imaging modality of choice. The study aims to determine the predictive value of CECT findings in diagnosing neck abscess, causes of neck abscess and the most common neck space involved in the local population. 84 consecutive patients clinically suspected to have neck abscess who underwent CECT and surgical confirmation of pus were included. Demographic and clinical data were recorded. 75 patients were diagnosed as having neck abscess on CECT; out of those 71 patients were found to have pus. Overall CECT findings were found to have a high sensitivity (98.6%) and positive predictive value (PPV) (94.7%) but lower specificity (67.2%) in diagnosing neck abscess. The CECT diagnostic criterion with the highest PPV is the presence of rim irregularity (96%). The most common deep neck space involved is the submandibular compartment, which correlates with the finding that odontogenic cause was the most common identifiable cause of abscess in the study population. Thus, in a patient clinically suspected of having neck abscess, CECT findings of a hypodense mass with rim irregularity are helpful in confirming the diagnosis and guiding clinical management.